Effects of metacognitive guidance on critical thinking disposition - Akyuz, Halil İbrahim; Yetik, Serap; Keser, Hafize (SynthesisHub Advance Scientific Research, 2015)
The present study investigated the effect of metacognitive guidance in an online learning environment on the students' critical thinking competency. The research was carried out using experimental design with pretest-posttest control groups. The research group of the study consisted of 60 students studying at Computer and Educational Teaching Department of Educational Sciences Faculty at Ankara University during the fall semester of 2011-2012. The 51 point California Critical Thinking Disposition Inventory was used to collect pretest-posttest data. In terms of total score of critical thinking tendency, the average score of the group that received critical guidance was found to be higher than the score of the control group. The metacognitive guidance offered to the students in the online learning environment has affected their critical thinking tendency in a positive way. Findings indicate that metacognitive guidance in online learning environments can be an effective tool in developing critical thinking among preservice teachers.
Keywords: Preservice teachers; Eğitim, Eğitim Araştırmaları; Online learning; Preservice teachers; Metacognitive guidance (Coaching); Critical thinking; Online learning; Metacognitive guidance (Coaching); Critical thinking; 4. Education; 3. Good health